Optimizing Patient Outcomes Through Sequential EGFR TKI Treatment in Asian Patients With EGFR Mutation-Positive NSCLC. (June 2022) - Liu, Rong; Zhou, Jianying; Ling, Xia
Patients from Asia with non-small-cell lung cancer (NSCLC) often have mutations in the epidermal growth factor receptor ( EGFR ) gene. While an increasing number of EGFR tyrosine kinase inhibitors (TKIs) are now available for patients with EGFR mutation-positive NSCLC, most patients inevitably develop resistance to the treatment. Evidence from clinical studies suggests that treatment outcomes and resistance mechanisms vary depending on the choice of TKI therapy in the first-line setting. Hence, it is important to develop optimal treatment sequencing strategies that can provide maximum survival benefit for the patient. In this review we present clinical evidence in Asian patients with NSCLC for various EGFR TKIs, with the goal of supporting the optimization of treatment sequencing.